Electromagnetic Mass and Violation of Newton’s Law - Acharya, Shreeram (Himalayan Physics, 2011)
Not available. Key words: Newton's Law The Himalayan Physics Vol.1, No.1, May, 2010 Page: 97-98 Uploaded Date: 28 July, 2011